Forthcoming events - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1988)
IKOFA 88 1 7th international Exposition of the Food Industry September 16-21, 1988 Muncher Messe und Austellungs Gesellschaft mbH Messegelande Postfach 12 1009 D-8000 Munich 12 GERMANY International Exposition on Food and Biological Advances in...